Kompensasi Kerugian Saat Masih Sengketa di Pengadilan Pajak - Muhammad Rifky Santoso (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2022)
To ensure that the value of loss compensation declared by the Taxpayer (WP) is correct, the tax authority conducts a tax audit. It is possible that the value of the loss compensation resulting from this tax audit is not approved by the taxpayer and is still being processed in the Tax Court. By using the case method from the Tax Court in Indonesia, it is known that the Taxpayer has taken legal action on the value of the loss compensation. In the 2014 tax year SPT PPh, the taxpayer suffered a loss and is still in the process of being appealed to the Tax Court. At the same time, taxpayers also filed an appeal process for the 2015 tax return with a dispute on compensation for losses from the 2014 tax year. For legal certainty and efficiency, it is better for taxpayers not to take legal action for the 2015 tax year, it is enough to wait for the decision on 2014 tax returns and the 2015 tax rectification returns that have been audited. Unfortunately, the Harmonization of Tax Regulation (formerly the KUP Law) does not allow taxpayers to correct the 2015 tax returns that have been audited. Therefore, it is necessary to revise the KUP Law so that taxpayers can correct the SPT that has been audited because it is influenced by the previous year's SPT whose examination results are known at a later date.